Detection of porcine respiratory coronavirus and transmissible gastroenteritis virus by an enzyme-linked immunosorbent assay - Cornaglia, E. (Vet Microbiol, 1994)
An enzyme-linked immunosorbent assay (ELISA) for the detection of transmissible gastroenteritis virus (TGEV) and porcine respiratory coronavirus (PRCV) was developed. A bovine TGEV-specific polyclonal antibody was purified by affinity chromatography with the TRIO Bioprocessing System and was used as the capture antibody, at a concentration of 1.5 μg/well. The F5.39 monoclonal antibody was obtained by the fusion of spleen lymphocytes from TGEV immunized mice with NS-1 myeloma cells. This mAb was used as a second antibody for the ELISA to detect TGEV in field cases, 53 intestinal samples were taken from pigs exhibiting clinical signs of transmissible gastroenteritis. All the positive samples detected by the ELISA were confirmed as positive by immunofluorescence or cell culture immunofluorescence. To study the ability of this ELISA to detect PRCV in nasal swabs and lung samples, 20 seven-day-old piglets were inoculated with a Quebec strain of PRCV. The ELISA was able to detect PRCV in both kinds of samples.